Pregabalin: Dose-Response Relationship in Generalized Anxiety Disorder - Boschen, M. J. (Pharmacopsychiatry, 2012)
Pregabalin is a structural analogue of the inhibitory neurotransmitter GABA. Although pregabalin has demonstrated efficacy in the treatment of generalized anxiety disorder (GAD) in a number of randomized controlled trials, there is little published data on the optimal dose for treating this condition. The objective of the current study was to examine the dose-response relationship for treatment of GAD with pregabalin.The current study pools results from previous fixed-dose treatment trials of GAD with pregabalin and uses curve-fitting statistical procedures to generate curvilinear regression lines as a synthesis of previous dose-response information.Peak reduction in anxiety symptoms was observed to occur at a dose of approximately 450 mg/day, with a small reduction in treatment effect beyond this dose. Treatment effect on psychic anxiety symptoms reached a peak at approximately 400 mg, with a reduction in efficacy beyond this dose. Somatic anxiety symptoms showed continued increase in therapeutic effect up to the maximum dose of 600 mg/day.Implications for psychiatric practice, limitations of the methodology and avenues for future research are discussed.
Keywords: pregabalin; generalized anxiety disorder; anxiety disorder; anxiety; dose-response curve